Der Proceβ in Yiddish, or The Importance of being Humorous - Bruce, Iris (TTR)

(untitled) (Association canadienne de traductologie, 1994)
AbstractDer Proceß in Yiddish, or the Importance of being Humorous — The article argues for a "humorous" Franz Kafka rather than a kajkaesque one and criticizes the "Kafka myth" which cristallized after WWII and emphasized foremost Kafka's existential anguish. Even before the war Max Brod as well as Walter Benjamin recognized the humorous dimension in Kafka's texts, much of which lies in word plays and gesture; otherwise, the humour in Kafka was largely ignored, especially after WWII. The focus in this article is on English, German and Yiddish cultural contexts and ideologies which have determined different readings/ translations of Kafka's texts. In particular, the article compares the pre-war English translation of Der Proceß by Edwin and Willa Muir, which contributes to the "Kafka myth," with a post-war Yiddish translation by Melech Ravitch, which highlights the novel's humorous qualities. Not only does the Yiddish translation place Kafka's novel within a culturally specific literary genre and suggest an alternate "Jewish" reading of the text; by drawing on both the English translation and the German original, Ravitch also "corrects" the anguish laden "Kafka myth" and constitutes a challenge to the rather humourless genre of the kafkaesque so widespread still in contemporary English and German speaking cultures.